2022
DOI: 10.1115/1.4055434
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Impact Psychological Safety in Engineering Student Teams? A Mixed-Method Longitudinal Investigation

Abstract: While psychological safety has been shown to be a consistent, generalizable, and multilevel predictor of outcomes in team performance across fields that can positively impact the creative process, there has been limited investigations of psychological safety in the engineering domain. Without this knowledge we do not know if or when fostering psychological safety in a team environment is most important. This study provides one of the first attempts at answering these questions through an empirical study with 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Still, existing research suggests the process of communicating, negotiating, refining, and selecting design ideas is informed by the personal characteristics of students who are participating, including sociocognitive factors such as their self‐efficacy for design tasks, team‐level factors such as psychological safety and climate, as well as student characteristics (e.g., race/ethnicity, gender) that carry performance expectations that preclude some students from full, equitable participation (Cole et al, 2022; Fowler & Su, 2018; Henderson, 2023). For example, in a case study of a cornerstone design team, Hirshfield (2018) described complex gender dynamics that shaped divisions of labor and contributions to the team, noting that the female student reported lower confidence, being talked down to, and being kept from doing technical engineering work by her male teammates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Still, existing research suggests the process of communicating, negotiating, refining, and selecting design ideas is informed by the personal characteristics of students who are participating, including sociocognitive factors such as their self‐efficacy for design tasks, team‐level factors such as psychological safety and climate, as well as student characteristics (e.g., race/ethnicity, gender) that carry performance expectations that preclude some students from full, equitable participation (Cole et al, 2022; Fowler & Su, 2018; Henderson, 2023). For example, in a case study of a cornerstone design team, Hirshfield (2018) described complex gender dynamics that shaped divisions of labor and contributions to the team, noting that the female student reported lower confidence, being talked down to, and being kept from doing technical engineering work by her male teammates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, early research has found psychological safety to significantly predict conflict and cohesion in engineering student teams at the individual and team levels (Beigpourian et al, 2019). Recent studies have investigated psychological safety in engineering student teams over time (Cole, Marhefka, et al, 2022; Cole, O'Connell, et al, 2022). Cole, Marhefka, et al (2022) and Cole, O'Connell, et al (2022) found that psychological safety was associated with the number of viable ideas generated by first‐year engineering student teams.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the qualitative portion of the study, deductive coding was used to better understand and explain the results obtained in the quantitative portion [12]. A codebook derived from the literature supporting CATME's survey design was used to guide the coding process (see Table 3) [5]. A random subset of ~20% of the responses from each section was extracted and then consolidated into a new dataset, randomized, and evenly split across the authors for coding so that each author would randomly code a similar number of responses from students in any section.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected included student reflections on their teamwork experience at the end of the semester and their sense of psychological safety in their teams as measured by a survey. Psychological safety has been shown to be an important indicator of the effectiveness of teams in engineering and other disciplines [5], [6]. Equitable teaming tools are intended to reduce stereotyping and task-assignment bias with the expected result of improving team dynamics and productivity [7].…”
Section: Study Intent and Supporting Literaturementioning
confidence: 99%